Neden 3x ^ 2 + 3 / x ^ 2 = 3 (x + 1 / x) ^ 2-6?

Neden 3x ^ 2 + 3 / x ^ 2 = 3 (x + 1 / x) ^ 2-6?
Anonim

Cevap:

Aşağıdaki kanıtı görmek

Açıklama:

Binom Formül Tarafından

# (A + b) ^ 2, a ^ 2 + 2ab + B ^ 2 #

alırız

3. (x ^ 2 + 1 / x ^ 2 + 2 * x * 1 / X) -6 = 3 (x ^ 2 + 1 / x ^ 2) + 6-6 = 3 (x ^ 2 + 1 / x ^ 2) #

Cevap:

Lütfen aşağıya bakın.

Açıklama:

# 3x ^ 2 + 3 / x ^ 2 #

= 3. (x ^ 2 + 1 / x ^ 2) #

= 3. (x ^ 2 + 2 x x x 1 / x + (1 / x) AD 2-2 x x x 1 / X) #

= 3. (burada (x + 1 / x) AD 2-2) #

= 3. (x + 1 / x) AD 2-6 #

# 3 (x + 1 / x) ^ 2-6 #

3. (x ^ 2 + 1 / x ^ 2 + 2) -6 #

Parentezleri aç, # 3x ^ 2 + 3 / x ^ 2 + 6-6 #

# 3x ^ 2 + 3 / x ^ 2 #